Correlation analysis of serum C1QTNF9 and Homo-Cys levels with the severity of coronary artery lesions (CHD): Serum C1QTNF9 and Homo-Cys levels in CHD - Wang, Rui; Zhang, Man; Ran, Lafang; Tang, Guozhang; Yu, Lu (Journal of Medical Biochemistry, 2026)
[Objective] To investigate the connections between the vulnerability of coronary atherosclerotic plaques and the severity of coronary artery lesions in patients with coronary heart disease (CHD) and the serum levels of C1q/tumor necrosis factor-related protein 9 (C1QTNF9), homocysteine (Homo-Cys), and D-dimer (D-D).[Methods] Research participants were 396 individuals with suspected coronary heart disease (CHD) who came to the hospital between June 2022 and October 2025 with symptoms like tightness and pain in their chest. Through coronary angiography (CAG) examination, The CHD group consisted of 248 patients with CHD, while the control group consisted of 148 people without CHD. The two patient groups' serum levels of C1QTNF9, Homo-Cys, and D-D were compared. Three types of CHD patients were identified based on the findings of the blood flow reserve fraction test: those with no plaque, those with stable plaque, and those with susceptible plaque. Using the Gensini scoring standards, the patients were divided into three groups according to the CAG examination results: low-risk (less than 20 points), medium-risk (20–40 points), and high-risk (more than 40 points). The patients were split into one lesion group, two lesion groups, and three or more lesion groups. Serum levels of C1QTNF9, Homo-Cys, and D-D were compared and associations were examined in CHD patients with varying coronary artery plaque stabilities, coronary artery lesion counts, and Gensini scores.[Results] The CHD group's serum C1QTNF9 level was lower than the control group's, despite the Homo-Cys and D-D levels being significantly greater (P
Keywords: Coronary heart disease; D-Dimer; Homocysteine; Vulnerable plaque degree of lesion